A 1‐to‐n way single‐ended‐to‐balanced substrate integrated waveguide filtering power splitter. Issue 7 (14th March 2020) - Shi, Jin; Shen, Zhidan; Xu, Kai
Abstract: An approach to 1‐to‐ n ( n = 3, 4…) way single‐ended‐to‐balanced filtering power splitter (SETBFPS) is proposed. The properly placed balanced ports with 0.5 λ g ( λ g is the substrate integrated waveguide [SIW] guided wavelength at f 0 ) space make the TE32nd 103 and TE32nd 105 modes of n 32nd‐mode SIW multimode resonators form differential‐mode (DM) passband of the SETBFPS. Compared with the state‐of‐art single‐ended‐to‐balanced power splitters, the proposed approach has all the functions of 1‐to‐ n way, filtering, and common‐mode (CM) suppression. A 1‐to‐3 way prototype is exemplified at 3.5 GHz with the minimum insertion loss (IL) of 0.09 dB, a fractional bandwidth (FBW) for a 15‐dB return loss of 35%, and a FBW for 15‐dB CM suppression of 52%. Low IL and wide bandwidth can be observed.